Penguatan Keuangan Sederhana dan Kontrol Kualitas Pada UMKM Makanan dan Minuman - Wijayati, Dewie Tri; Kautsar, Achmad; Amelia, Ratih; Jacobis, Riedel Paulus (Abimanyu : Jornal of Community Engagement, 2025)
This community service activity aims to improve the capacity and competence of Human Resources (HR) management in the digital era for statue craftsmen in Trowulan District, Mojokerto City. This training is designed as a response to the needs of craftsmen to adapt to technological developments and digitalization that are increasingly affecting various sectors, including the craft industry. The training held in Mojokerto City includes several main materials, namely: technology-based HR management, utilization of digital media for marketing, digital HR data management, and development of communication skills for more effective collaboration. The methods used include lectures, interactive discussions, simulations, and direct practice, so that participants can easily understand and apply the material provided. The results of this activity show that the statue craftsmen have high enthusiasm for the application of digital technology in managing their businesses. Participants acknowledged their increased understanding in utilizing digital platforms to support HR management, expand marketing reach, and increase work efficiency. This activity is expected to be the first step in the digital transformation of the statue craft industry in Mojokerto, as well as have a positive impact on increasing the competitiveness and sustainability of craftsmen's businesses in the era of globalization.